Protecting the Human Right to Water through the Regulation of Multinational Enterprises - Krajewski, Markus (The Regulation of the Global Water Services Market, 2017)
The activities of multinational enterprises can have significant impact on the provision of clean and sufficient water in all parts of the world. The activities of private enterprises in the water market and in other business sectors are regulated by the domestic legal system. However, often these regulations may not be sufficient due to regulatory weaknesses, the transnational character of the respective companies or because of their sheer economic power. Regulating multinational corporations through international norms and instruments is therefore an increasingly important element of global economic governance. This paper addresses the human rights-based regulation of multinational enterprises as an instrument to protect the human right to water as well as an element of the global regulatory framework of the water market. The chapter sketches the conceptual and institutional framework of such an approach and then analyses four case studies brought before different National Contact Points which are vested with the implementation of the OECD Guidelines for Multinational Enterprises. Based on these case studies a few preliminary conclusions will be drawn. It will also be shown that the soft case law of the NCPs when implementing OECD Guidelines provides rich empirical material which could be used to develop further the legal principles regulating the activities of multinational companies in particular in areas which may affect human right
Keywords: Right to Water; Human rights and business; OECD Guidelines for Multinational Enterprises; OECD National Contact Points